2020
DOI: 10.1038/s41467-020-20222-z
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic regulator Mll1 is required for Wnt-driven intestinal tumorigenesis and cancer stemness

Abstract: Wnt/β-catenin signaling is crucial for intestinal carcinogenesis and the maintenance of intestinal cancer stem cells. Here we identify the histone methyltransferase Mll1 as a regulator of Wnt-driven intestinal cancer. Mll1 is highly expressed in Lgr5+ stem cells and human colon carcinomas with increased nuclear β-catenin. High levels of MLL1 are associated with poor survival of colon cancer patients. The genetic ablation of Mll1 in mice prevents Wnt/β-catenin-driven adenoma formation from Lgr5+ intestinal stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 75 publications
3
46
0
Order By: Relevance
“…Last, the ability of β-catenin and KMT2A to impinge on cancer stemness is of particular interest and highlights a genetic interaction between the two proteins. Deletion of KMT2A causes the loss of stem cell properties of tumorigenic organoids, characterized by the differentiation phenotype and reduced expression of LGR5, as confirmed by recent work ( 52 ). The transcriptional profile of KMT2A-ablated CRC cells also indicates a marked down-regulation of stem cell markers [LGR5 and achaete scute-like 2 (ASCL2)] and a concurrent up-regulation of epithelial differentiation markers (KRT20, KRT19, carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), and CDKN1A).…”
Section: Discussionsupporting
confidence: 75%
“…Last, the ability of β-catenin and KMT2A to impinge on cancer stemness is of particular interest and highlights a genetic interaction between the two proteins. Deletion of KMT2A causes the loss of stem cell properties of tumorigenic organoids, characterized by the differentiation phenotype and reduced expression of LGR5, as confirmed by recent work ( 52 ). The transcriptional profile of KMT2A-ablated CRC cells also indicates a marked down-regulation of stem cell markers [LGR5 and achaete scute-like 2 (ASCL2)] and a concurrent up-regulation of epithelial differentiation markers (KRT20, KRT19, carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), and CDKN1A).…”
Section: Discussionsupporting
confidence: 75%
“…Elevated H3K4me3 methylation and transcriptional activity has been correlated to Yap (40)(41)(42). Since the histone methyltransferase Mll1 has been shown to take part in reprogramming processes (43)(44)(45), and we have recently demonstrated a role of Mll1 and H3K4me3 in conferring a cancer stem cell fate in salivary gland and colon tumors (46,47), we investigated whether Mll1 is involved in the regenerative cell state of NICD/p53 −/− organoids. In the small intestinal epithelium we detected pronounced H3K4me3 in the crypt cell compartment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the role of Yap in cancer is well established (15), the implication of Mll1 and histone modifiers in colon cancer is an emerging field of research (47). Recent experiments in cell cultures and in xenografted tumor cells showed that Mll1 is crucial in solid cancer cells (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spindlin1 is expressed in Lgr5 + intestinal stem cells and is required for self-renewal. It also promotes cancer stemness in a β-catenin-dependent manner ( Su et al, 2014 ; Grinat et al, 2020 ). Previously, a report had shown that the MLL1/CBP/β-catenin complex promotes tumor initiation and metastasis in the head and neck squamous cell carcinoma by increasing the activation associated mark H3K4me3 at the promoters of target genes ( Qiang et al, 2016 ).…”
Section: Wnt Signaling and Epigenetic Regulationmentioning
confidence: 99%